No Room for Secrets - Lumley, Joanna (London Penguin Books, 2004)
The author uses the unique structure of a tour through her home to tell you about her life. Elements of and objects in each room help her recall; people, places, plays, films and TV series she has worked on.
Include Color Illustration
Keywords: Television actors and actresses -- Great Britain -- Lumley, Joanna